KEJADIAN REAKSI KUSTA DI PUSKESMAS KOTA PONTIANAK PERIODE 2008-2013 - ., Qory Irsan (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Leprosy reaction is an acute episode during course of leprosy disease due to alteration in bodyâ€™s immune system. Leprosy reaction can occurs before, during or after treatment of leprosy. Objective: To know about description of leprosy reaction in Puskesmas Kota Pontianak 2008-2013 period. Methods: This study used desciptive cross sectional method. The data was fetched by identify the medical record and interview leprosy patient. Results: 37 of 56 subjects constituted leprosy reaction. From those number, 97,2 % were Multibasiler, 75,6 % constitued reversal reaction, 70,2 % having reaction during treatment of leprosy, 37,8 % had psychological stress before reaction happen, 51,3 % presented mild reversal reaction, 43,2 % used paracetamol dan 83,7 % took a rest to treat the reaction, and 78,3 % were in well condition after taking reaction treatment. Moreover, most fof them are 15-34 years old (43,2 %) and male (72,9 %). Conclusions: Most of leprosy patient have had leprosy reaction, especially during the leprosy treatment, with presentation of mild reversal reaction. Keywords: Leprosy reaction, reversal reaction Descriptions: 1.Â  Medical Education Program, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan. 2. Department of Dermatology and Veneral Disease, Educational Hospital of Tanjungpura University, Pontianak, West Kalimantan 3. Department of Community, Medicine, Family Medicine and Public Health, Faculty of Medicine, Tanjungpura University, Pontianak, West Kalimantan